Erectile dysfunction (ED) after ischemic stroke: association between prevalence and site of lesion - Koehn, Julia; Crodel, Carl; Deutsch, Martina; Kolominsky-Rabas, Peter; Hoesl, Katharina M.; Köhrmann, Martin; Schwab, Stefan; Hilz, Max-Josef (Clinical Autonomic Research, 2015)
Stroke may cause or worsen erectile dysfunction (ED). Post-stroke ED prevalence and association with stroke location are not well established. Therefore, we assessed post-stroke ED prevalence in relation to ischemic lesion locations and stroke severity.In 57 men (62.6 ± 10.5 years) who had ischemic stroke within 24 months prior to evaluation, we used the five-item International Index of Erectile Function questionnaire (IIEF5) to evaluate ED prevalence after stroke and retrospectively 3 months prior to stroke. IIEF5 scores range from 5 to 25; scores below 22 indicate ED. We estimated stroke severity upon hospital admission, using the National Institute of Health Stroke Scale (NIHSS), and determined stroke location from cranial computed tomography or magnetic resonance imaging. We compared pre- and post-stroke results with those of 22 control persons (61.7 ± 11.2 years), calculated correlations between IIEF5 scores and NIHSS scores, and compared ED prevalence with stroke locations (significance: p < 0.05).ED was reported by 45/57 patients after stroke, 26/57 patients before stroke, and 6/22 control persons. Patients' IIEF5 values were significantly lower [median 16 interquartile range (IQR) 3.5-20.5] after than before stroke (median 23, IQR 19.0-24.0) and lower than in controls (median 24, IQR 19.8-25.0). Pre- and post-stroke IIEF5 scores did not correlate with the patients' NIHSS scores at stroke onset (p > 0.05). ED was associated with middle cerebral artery infarction in 27/34, posterior cerebral artery infarction in 4/5, anterior cerebral artery infarction in 1/1, basal ganglia infarction in 3/3, brain stem infarction in 8/10, cerebellar infarction in 2/5, and lesions in more than one region in 1/1 patients.Disruption of the central network assuring erection might contribute to increased ED severity and prevalence after stroke. Anti-erectile effects of functional and psychological impairment or medication added after stroke may also contribute to ED but must be evaluated in larger patients groups.
EVALuna2:22368

Insular multiple sclerosis lesions are associated with erectile dysfunction - Winder, Klemens; Linker, Ralf; Seifert, Frank; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Hoesl, Katharina M.; Hilz, Max-Josef (Journal of Neurology, 2018)
Erectile function (EF) is frequently compromised in men with multiple sclerosis (MS). Functional neuroimaging in healthy men identified a network of brain areas, such as the insula, visual and somatosensory association areas, cingulate gyrus, prefrontal cortex, as well as subcortical regions, contributing to EF. This study intended to determine associations between EF deterioration during MS and cerebral MS-associated lesion sites. In 31 men with MS (mean age 38.2 ± 11.2 years), we evaluated MS-related EF deterioration by comparing scores of the 5-item International Index of Erectile Function-5 questionnaire (IIEF5) at the time of study and retrospectively, 3 months prior to MS diagnosis, by calculating score differences as DeltaIIEF5 (DeltaIIEF5 score < 0 indicated EF deterioration). To assess the impact of confounding factors of EF, patient age, disease duration, disease severity, depressiveness, bladder and bowel symptoms, and total cerebral MS lesion volume were correlated with DeltaIIEF5 scores (Spearman rank correlation) and compared between patients with and without EF deterioration (t tests or Mann-Whitney U test). MS lesions were assessed on T2-weighted magnetic resonance imaging (MRI; 1.5 or 3 T). We determined the lesion overlap (prevalence of identical lesion sites among patients), subtracted lesion overlaps in patients without EF deterioration from overlaps in patients with EF deterioration, and compared DeltaIIEF5 scores voxel-wise between patients with and without lesions in a given voxel (t test; significance: p < 0.05). In 14 patients (45.2%), DeltaIIEF5 scores indicated EF deterioration. DeltaIIEF5 scores were not associated with age (ρ = 0.06; p = 0.74), disease duration (ρ = 0.26; p = 0.15), disease severity (ρ = - 0.19; p = 0.31), depressiveness (ρ = 0.07; p = 0.72), bladder symptoms (ρ = - 0.11; p = 0.57), bowel symptoms (ρ = 0.17; p = 0.37), and total lesion volume (ρ = - 0.13; p = 0.47). The voxel-wise analysis showed associations between EF deterioration and MS lesions primarily in the bilateral, and predominantly left juxtacortical insular region. In conclusion, MS lesions particularly in the left insular region, which is activated with sexual arousal, contribute to erectile dysfunction.
EVALuna2:34021

Interrelation of depression, sexual dysfunction and disease severity in patients with multiple sclerosis - Hoesl, K.; Roy, Sankanika; Wang, Ruihao; Intravooth, Tassanai; Deutsch, Martina; Winder, K.; Lee, De-Hyung; Linker, Ralf; Hilz, M. J. (2017)
EVALuna2:22574

Neuroanatomic Correlates of Female Sexual Dysfunction in Multiple Sclerosis - Winder, Klemens; Linker, Ralf; Seifert, Frank; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Hoesl, Katharina M.; Hilz, Max-Josef (Annals of Neurology, 2016)
This study intended to determine associations between alterations of female sexual arousal as well as vaginal lubrication and the site of cerebral multiple sclerosis (MS) lesions.In 44 women with MS (mean age: 36.5 ± 9.9 years), we assessed their medical history and evaluated sexual function using the Female Sexual Function Index scores for arousal and vaginal lubrication. We determined potential confounding factors of sexual dysfunction: age; disease duration; physical disability; depression; bladder or urinary dysfunction; and total volume of cerebral lesions. Arousal and lubrication scores were correlated with one another and with potential confounding factors. Cerebral MS lesions were recorded on imaging scans. A voxel-based lesion symptom mapping (VLSM) analysis adjusted for confounding variables was performed correlating cerebral sites of MS lesions with arousal and lubrication scores.Decreased arousal scores correlated with decreased lubrication scores; decreased lubrication scores were associated with bladder or urinary symptoms. Arousal and lubrication scores were not associated with any other variables. Multivariate VLSM analysis, including arousal and lubrication scores as covariables of interest, showed right occipital lesions associated with impaired arousal and left insular lesions associated with decreased lubrication. Impaired lubrication remained associated with left insular lesions after adjustment for bladder or urinary dysfunction.Our data indicate that impaired female sexual arousal is associated with MS lesions in the occipital region, integrating visual information and modulating attention toward visual input. Impaired lubrication correlated with lesions in the left insular region, contributing to mapping and generating visceral arousal states. Ann Neurol 2016;80:490-498.
EVALuna2:22501

Sexual Dysfunction Seems to Trigger Depression in Female Multiple Sclerosis Patients - Hoesl, Katharina M.; Deutsch, Martina; Wang, Ruihao; Roy, Sankanika; Winder, Klemens; Niklewski, Guenter; Lee, De-Hyung; Linker, Ralf; Hilz, Max-Josef (European neurology, 2018)
BACKGROUND: In women with multiple sclerosis (MS), depression and sexual dysfunction (SD) are common. Whether SD promotes depression or vice versa remains unclear despite therapeutic relevance. Therefore, we aimed to assess whether SD more likely triggers depression or vice versa. METHODS: In 83 female MS patients and 21 age-matched healthy women, we assessed depression, using the Beck Depression Inventory-V (BDI-V), and SD using the Female Sexual Function Index (FSFI). We diagnosed depression with BDI-V-scores >35 and SD with FSFI scores < 26.55. We divided patients into groups with and without SD, with and without depression. Between groups, we compared prevalence of SD and depression (Fisher's-exact-test), age, MS-duration, MS-severity, BDI-V-, and FSFI scores (Mann-Whitney U-test; significance: p < 0.05). RESULTS: A total of 37/83 MS patients and 1/21 controls had SD; 28/83 patients and 3/21 controls had depression; 51.4% patients with SD but only 19.6% without SD had depression (p = 0.003). SD was present in 67.9% depressed and 32.7% non-depressed patients. BDI-V-scores were higher in patients with SD than in patients without SD. FSFI scores were lower in depressed than non-depressed patients. CONCLUSION: In conclusion, SD was more common than depression. SD afflicted 67.9% depressed MS patients and was also more common in non-depressed MS patients than controls. SD may occur independently from depression while increased depressiveness seems linked to coexistent SD.
EVALuna2:35522

Site and size of multiple sclerosis lesions predict enhanced or decreased female orgasmic function - Winder, Klemens; Seifert, Frank; Koehn, Julia; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Linker, Ralf; Hilz, Max-Josef (Journal of Neurology, 2015)
Neuroimaging identified brain areas involved in female orgasm. In women with multiple sclerosis (MS), associations between orgasmic function and the site and size of MS-related magnetic resonance imaging (MRI) changes are undetermined. This study intended to correlate MS-associated cerebral lesion load and location with clinical scores of female orgasmic function. In 50 women with MS (mean age 37.0 ± 9.9 years), we assessed Female Sexual Function Index (FSFI) scores for orgasmic frequency, difficulty and satisfaction. We determined disease duration, Expanded Disability Status Scale (EDSS) scores, and cerebral MS-lesion load and location using T2-weighed 1.5 T MRIs. We correlated FSFI scores for orgasm with patient age, disease duration, EDSS scores, and cerebral MS-lesion load (Spearman rank correlation; significance: p < 0.05). FSFI scores for orgasm correlated inversely with MS-lesion load in the left temporal periventricular white matter and right middle-inferior occipital area, but directly with MS-lesion load in the right frontal primary motor cortex, left prefrontal/inferior frontal cortex, right amygdala, left temporal middle-inferior and fusiform areas, and midbrain. FSFI scores for orgasm did not correlate with patient age, disease duration and EDSS scores (p > 0.05). In conclusion, our results indicate that MS-lesions in left temporal periventricular and right visual association areas deteriorate orgasmic function. In contrast, direct correlations between frontotemporal or midbrain lesions and higher FSFI scores, indicating enhanced or disinhibited orgasmic function, suggest that these brain regions normally buffer orgasmic responses. Moreover, our results indicate that orgasmic dysfunction in women with MS evolves independently of disease duration and physical disability.
EVALuna2:22361